MIĘDZY MONARCHIĄ STANOWĄ A DEMOKRACJĄ SZLACHECKĄ. ZNACZENIE PRZYWILEJÓW NIESZAWSKICH W PERIODYZACJI DZIEJÓW POLSKI - Sobotka, Roman (Zeszyty Prawnicze, 2016)
BETWEEN ESTATE MONARCHY AND DEMOCRACY OF THE GENTRY. THE IMPORTANCE OF THE PRIVILEGES OF NIESZAWA FOR THE PERIODIZATION OF HISTORY OF POLAND Summary In his article the author deals with the issue of periodization of the history of the Polish political system. In particular the author concentrates on one of the privileges issued by the king Casimir IV Jagiellon in 1454 in Nieszawa. According to this privilege the king should not legislate or summon the nobility to war without a local diet assembly (sejmik). In the opinion of some authors who deal with the issue it was the time (the year 1454) when the importance of local diets was raised and the position of the nobility within the structure of the authorities of the Kingdom of Poland was settled. The author emphasises that the privilege concerned only Wielkopolska and analyses the information about militia calling out in the second half of the 15th century. On the basis of the sources gathered, the author makes the conclusion that the article mentioned had not been put in force as it was plenary or provincial diets that made decisions about militia calling or taxes, and not local diets. Therefore, in the author’s opinion the date 1454 does not make any decisive moment for the history of the Polish political system.